Oral microbiome as a co-mediator of halitosis and periodontitis: a narrative review - Lee, Yeon-Hee; Hong, Ji-Youn (Frontiers in Oral Health, 2023)
Halitosis or oral malodor is an unpleasant odor from the oral cavity. However, although patients with periodontitis often complain of halitosis, their relationship has not been fully elucidated.We reviewed previous literature based on the hypothesis that the relationship between halitosis and periodontitis is mediated by the oral microbiome.This narrative review sought to provide insight into the causative role of the oral microbiome in influencing halitosis and periodontitis. In addition, we tried to deepen knowledge related to the relationship between halitosis and periodontitis generated by the oral microbiome accumulated over the past 40 years.From 1984 to 2023, a total of 107 papers that carefully and scientifically dealt with halitosis and periodontitis were included in this narrative review. Based on previous results, halitosis and periodontitis were closely related. For decades, researchers have taken an intriguing approach to the question of whether there is a relationship between halitosis and periodontitis.Central factors in the relationship between halitosis and periodontitis include volatile sulfur compounds (VSCs), the oral microbiota that produce VSCs, and the inflammatory response.Taken together, the more severe periodontitis, the higher the level of VSC in halitosis, which may be mediated by oral microbiome. However, the relationship between the occurrence, maintenance, and exacerbation of periodontitis and halitosis is not a necessary and sufficient condition for each other because they are complex interplay even in one individual.